2019
DOI: 10.1038/s41598-019-42674-0
|View full text |Cite
|
Sign up to set email alerts
|

Limb linkage rehabilitation training-related changes in cortical activation and effective connectivity after stroke: A functional near-infrared spectroscopy study

Abstract: Stroke remains the leading cause of long-term disability worldwide. Rehabilitation training is essential for motor function recovery following stroke. Specifically, limb linkage rehabilitation training can stimulate motor function in the upper and lower limbs simultaneously. This study aimed to investigate limb linkage rehabilitation task-related changes in cortical activation and effective connectivity (EC) within a functional brain network after stroke by using functional near-infrared spectroscopy (fNIRS) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 71 publications
0
26
0
1
Order By: Relevance
“…Another study showed that bilateral SMA activation was increased after intensive rehabilitation of postural balance ( 81 ). Yet, others suggested that plastic reorganization of cognitive resources serves to compensate for impairment in stroke patients during motor rehabilitation tasks ( 82 ). However, such studies of cortical balance and recovery using EEG were not carried out with hemianopic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that bilateral SMA activation was increased after intensive rehabilitation of postural balance ( 81 ). Yet, others suggested that plastic reorganization of cognitive resources serves to compensate for impairment in stroke patients during motor rehabilitation tasks ( 82 ). However, such studies of cortical balance and recovery using EEG were not carried out with hemianopic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Functional brain connectivity and activation patterns have been assessed with fNIRS in patients after stroke during motor rehabilitation tasks 53 and motor preparation for gait rehabilitation. 54 Because fNIRS allows complex movement in unconstrained environments, it may be used with feedback to facilitate learning in motor control 55 and even in neurofeedback settings to control prosthetic limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Data preprocessing was performed after delta HbO2 signals were obtained. We used the moving average filter was 3 s (Huo et al, 2019). A processing method based on moving standard deviation and cubic spline interpolation was then applied to remove motion artifacts (Scholkmann et al, 2010).…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%